2005
DOI: 10.1104/pp.104.050187
|View full text |Cite
|
Sign up to set email alerts
|

Insect-Induced Conifer Defense. White Pine Weevil and Methyl Jasmonate Induce Traumatic Resinosis, de Novo Formed Volatile Emissions, and Accumulation of Terpenoid Synthase and Putative Octadecanoid Pathway Transcripts in Sitka Spruce  

Abstract: Stem-boring insects and methyl jasmonate (MeJA) are thought to induce similar complex chemical and anatomical defenses in conifers. To compare insect-and MeJA-induced terpenoid responses, we analyzed traumatic oleoresin mixtures, emissions of terpenoid volatiles, and expression of terpenoid synthase (TPS) genes in Sitka spruce (Picea sitchensis) following attack by white pine weevils (Pissodes strobi) or application of MeJA. Both insects and MeJA caused traumatic resin accumulation in stems, with more accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
320
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(335 citation statements)
references
References 36 publications
9
320
1
4
Order By: Relevance
“…To the best of our knowledge, diterpenoids with a hydroxyl group at carbon-13 have not been found in previous analyses of Norway spruce resin or the resin of other spruce species (30,31). Whether their apparent absence is due to enzymatic or non-enzymatic dehydration in planta or to their sensitivity to dehydration ex planta in the process of resin extraction and analysis is not known and will be difficult to resolve.…”
Section: Discussionmentioning
confidence: 91%
“…To the best of our knowledge, diterpenoids with a hydroxyl group at carbon-13 have not been found in previous analyses of Norway spruce resin or the resin of other spruce species (30,31). Whether their apparent absence is due to enzymatic or non-enzymatic dehydration in planta or to their sensitivity to dehydration ex planta in the process of resin extraction and analysis is not known and will be difficult to resolve.…”
Section: Discussionmentioning
confidence: 91%
“…These results agree with a role of DRAs in constitutive conifer defense. Previous studies with Sitka spruce showed that MJ treatment mimics insect attack on trees (14). In loblolly pine, transcripts hybridizing with PtAO and PtLAS were increased in stem bark and xylem upon MJ treatment as part of the induced resin terpenoid defense (Fig.…”
Section: De Novo Diterpenoid Formation In Metabolically Engineered Yementioning
confidence: 96%
“…Organic solvents were then completely evaporated under N 2 , and dried compounds were dissolved in 50 l of diethyl ether. Diterpenoids were analyzed by GC-MS by using a 6890 GC-MSD system (70 eV, Agilent Technologies, Palo Alto, CA) with a DB1 capillary column (0.25 mm ϫ 0.25 m ϫ 30 m, J & W Scientific, Folsom, CA) (14). Injections of 2-l samples were splitless at 220°C with a column flow of 1 ml of He͞min.…”
Section: Constructs For P450 Expression In Yeastmentioning
confidence: 99%
“…These defenses consist of resin exudation that pitches out or delays attacking adults, and allelochemicals, particularly monoterpenes, that repel or kill the adults, prevent egg hatch, and inhibit or kill their symbionts (18)(19)(20). Monoterpenes occur at relatively low concentrations in constitutive (preattack) phloem, but are rapidly biosynthesized at the point of attack and accumulate to toxic levels within a few days (21)(22)(23). Bark beetles can overwhelm these barriers through pheromone-mediated mass attacks, in which large numbers of both sexes land on selected trees and tunnel into their tissues.…”
mentioning
confidence: 99%